Impacts of CAP reforms on farm structures and performance disparities: An agent-based approach - Amanda Sahrbacher (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2012)
The objective of this work is to investigate how Common Agricultural Policy's (CAP) direct payments influence the development of farm structures and therefore performance and income disparities between farms. In this study the focus is put on the comparison of impacts of changes in direct payments distribution on the agricultural sector considering 1) the decoupling model, i.e. either a regional area payment, a historic payment or a hybrid payment system from 2005; 2) the level and design of modulation, i.e. cuts in Pillar I payments relative or not to farm size and; 3) yearly cuts in Pillar I payments for all farms from 2013 parallel to increases in Pillar II payments. Outcomes of policy changes are analysed regarding their impact on farm structures, land use, land markets and agricultural production. Distributive effects of direct payments and agricultural incomes among farms are compared. The analyses performed in this study provide a panorama of impacts of CAP reforms on the agricultural sector. – – Ziel der Arbeit ist es zu untersuchen, wie die Direktzahlungen der Gemeinsamen Agrarpolitik (GAP) die Entwicklung der Betriebsstrukturen und dadurch Leistungs- und Einkommensdisparitäten zwischen den Betrieben beeinflusst. Der Schwerpunkt dieser Arbeit liegt im Vergleich der Auswirkungen der Verteilung der Direktzahlungen auf die Landwirtschaft. Dabei werden folgende drei Politikmaßnahmen betrachtet: 1) die Art der Entkopplung der Direktzahlungen im Rahmen der Fischler Reform, d.h. Regionalmodel, Betriebsmodel bzw. Hybridmodel; 2) das Niveau und die Ausgestaltung der Modulation, d.h. die Kürzung der Direktzahlungen in Abhängigkeit der Betriebsgröße bzw. unabhängig davon und 3) eine schrittweise Reduzierung der Direktzahlungen (1. Säule) ab 2013 für alle Betriebe parallel zu einer Aufstockung der Zahlungen der zweiten Säule. In der Analyse dieser Politiken werden insbesondere die Auswirkungen auf die Betriebsstrukturen, die Landnutzung, den Bodenmarkt und die Produktion berücksichtigt. Des Weiteren werden Auswirkungen auf die Verteilung der Direktzahlungen und Einkommen zwischen den Betrieben untersucht. Die durchgeführten Untersuchungen geben somit einen Überblick über die Auswirkungen der letzten GAP-Reformen auf die Landwirtschaft.
urn:nbn:de:gbv:3:2-18740
Keywords: 330; EU-Agrarpolitik; Reform; Wirkungsanalyse; Landwirtschaftliches Betriebssystem; Unternehmenserfolg; Agrareinkommen; Agentenbasierte Modellierung; EU-Staaten